THE INFLUENCE OF THE E-FILING IMPLEMENTATION, TAXATION SOCIALIZATION, AND TAX PENALTIES ON INDIVIDUAL TAXPAYER COMPLIANCE IN KPP PRATAMA JAKARTA TIMUR - Hamilah, Hamilah; Aliza, Salsabilla (Dinasti International Journal of Management Science, 2021)
This study aims to analyze and give empirical evidence on the effect of the application of e-filling, the socialization of taxation, and tax penalties on tax compliance. Theoretically, this research can provide an understanding and insight regarding the influence of the application of e-filling, the socialization of taxation, tax penalties and, individual taxpayer compliance. Practically, this research can provide additional knowledge to the student and society-related factors that influence taxpayer compliance. This research is a quantitative research with accidental sampling as sampling technique, and using the calculation of computerized SPSS version 25. The results showed that the application of E-Filling (X1), the Socialization of Taxation (X2), and Sanctions Taxation (X3) together significantly influence the taxpayer Compliance (Y). The adjusted R-Square value of 0.765 with a coefficient of determination stated that the E-Filing implementation, the Socialization of Taxation, and Tax penalties jointly contribute to the taxpayer compliance by 76,5%. The rest of 23.5% is influenced by other variables outside the research model.